Neighborhood dynamics and the housing price effects of spatially targeted economic development policy - Douglas J. Krupka; Douglas S. Noonan (Institute for the Study of Labor (IZA), 2009)
Neighborhoods are the result of a complicated interplay between residential choice, housing supply and the influences of the larger metropolitan system on its constituent parts. We model this interplay as a system of reduced-form equations in order to examine the effects of a generous spatially targeted economic development program (the federal Empowerment Zone program) on neighborhood characteristics, especially housing values. This system of equations approach allows us to compute direct effects of the policy intervention as well as the effects mediated through non-price channels such as changes in the housing stock or neighborhood demographics. In the process, we are able to shed light on the rich simultaneity among neighborhood characteristics, including housing prices.
urn:nbn:de:101:1-20090825470
Keywords: R0; R21; R31; R38; R58; 330; Economic development; simultaneity; Nachbarschaftsökonomie; Ländliche Entwicklungsplanung; Wirkungsanalyse; Immobilienpreis; USA